Pengaruh Kualitas Event terhadap Kepuasan Pengunjung pada MTQ Ke 56 Kota Medan Tahun 2023 - Nur Jannah Nasution; Efni Siregar (JURNAL RISET MANAJEMEN (JURMA), 2024)
Musabaqah Tilawatil Qur'an (MTQ) is a book reading competition Al-Qur'an with mujawwad reading, namely recitation of Al-Qur'an that follows the legal rules of tajwid, the art of song and sound, and reading with adab recitations. In organizing an event, the important thing that must be considered by the organizers is the implementation of structured activities in order to increase visitor satisfaction with the event being held. The excellence of an event is not only determined by the performers, but also must be supported by the quality of the event. The quality of the event (entertainment, performance, staff quality, physical surroundings) plays a very important role because it is assessed based on visitor satisfaction. If the quality of the event is good, the visitors who come will be happy, satisfied, and will revisit the next MTQ event. The purpose of this study was to find out whether there was an effect of event quality on visitor satisfaction at the 56th MTQ in Medan City in 2023. This study used quantitative research with a sample of 100 respondents. The analytical method in this study is multiple linear regression with partial hypothesis testing (t test) and simultaneous testing (f test). From the test results of this study, it was found that partially the variable quality of event performance (X₁), entertainment (X₂), staff quality (X₃), physical surroundings (X₄) simultaneously had a positive influence on visitor satisfaction.